Insights on Embolic Protection, Repositioning, and Stroke: A Subanalysis of the RESPOND Study - Julia Seeger; Volkmar Falk; David Hildick-Smith; Sabine Bleiziffer; Daniel J. Blackman; Mohamed Abdel-Wahab; Dominic J. Allocco; Ian T. Meredith; Jochen Wöhrle; Nicolas M. Van Mieghem (Journal of Interventional Cardiology)
RESPOND is a prospective, single-arm study enrolling 1014 transcatheter aortic valve replacement (TAVR) patients. The objective of this analysis is to assess the impact of cerebral embolic protection (CEP) devices and prosthetic valve repositioning on the risk of neurologic complications in patients treated with the fully repositionable Lotus Valve in the RESPOND postmarket study. Valve repositioning and CEP use were at the operators’ discretion. Stroke events were adjudicated by an independent medical reviewer. This analysis assessed the baseline differences among patients according to CEP use and valve repositioning and evaluated the neurological complications at 72 hours after TAVR, hospital discharge, and 30-day follow-up. A multivariate analysis was performed to identify the potential predictors of stroke. Of the 996 patients implanted with the Lotus Valve (mean age: 80.8 years, 50.8% female, STS score 6.0 ± 6.9), 92 cases (9.2%) used CEP. The overall rate of acute stroke/transient ischemic attack (TIA) was 3.0% at 72 hours after TAVR. The 72-hour stroke/TIA rate was 1.1% in patients who had CEP and 3.2% in those who did not. Use of CEP was associated with a 2.1% absolute reduction in the risk of acute neurological events (relative risk reduction: 65.6%), although the difference was not statistically significant (p=0.51). Repositioning of the Lotus Valve occurred in 313/996 procedures (31.4%). The 72-hour rate of stroke/TIA was similar in patients who had valve repositioning (2.9%) compared with those who did not (3.1%; p=0.86). The selective use of a CEP device in the RESPOND study was associated with a nonsignificantly lower risk for stroke within 72 hours. The use of the repositioning feature of the Lotus Valve did not increase the stroke risk.